2020
DOI: 10.11604/pamj.2020.37.61.21123
|View full text |Cite
|
Sign up to set email alerts
|

Stretched penile length and total serum testosterone in term male neonates

Abstract: Introduction the reference values of stretched penile length vary with different ethnic group. There is paucity of data on the reference range of total serum testosterone in neonates especially in Africa. This study therefore was to determine the normal stretched penile length, total serum testosterone levels in term male newborns and to correlate them with anthropometric parameters. Methods this was a prospective cross-sectional study. One hundred and twenty-four conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(34 reference statements)
0
5
1
Order By: Relevance
“…6 In the current study, our finding of mean SPL as 3.28 ± 0.42 cm for all gestational age is closely similar with the mean SPL of babies from other African countries (Table 3). [11][12][13]18,19 On the other hand, our finding is lower than an earliest publication on penile standards for American newborns by Feldman et al which reported a larger (3.5 ± 0.7 cm) penile length for full-term infants. 8 Studies that employed a similar methodology reported different penile sizes for Asian population as it was summarised in Table 3.…”
Section: Key Notescontrasting
confidence: 92%
“…6 In the current study, our finding of mean SPL as 3.28 ± 0.42 cm for all gestational age is closely similar with the mean SPL of babies from other African countries (Table 3). [11][12][13]18,19 On the other hand, our finding is lower than an earliest publication on penile standards for American newborns by Feldman et al which reported a larger (3.5 ± 0.7 cm) penile length for full-term infants. 8 Studies that employed a similar methodology reported different penile sizes for Asian population as it was summarised in Table 3.…”
Section: Key Notescontrasting
confidence: 92%
“…The implication of this is that irrespective of age, most penile glans has about same size. This is explained by the fact that penile size is about a constant in infancy due to a steady state of serum testosterone required for penile growth ( 14 , 15 ). It becomes a disincentive for using age to determine the appropriate size of Plastibell in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…In newborn girls, the length of the clitoris does not seem to be dependent on gestation and a newborn with a length greater than 8mm requires further evaluation 40 . Micropenis is defined as a stretched penile length of less than 2.5SD from the mean and based on contemporary studies from a wide range of countries, a stretched penile length of less than 2cm would represent a reasonable cut off for micropenis in the newborn 34,41–45 . In approximately 25% of affected cases, XY DSD is part of a complex multi‐system condition 37,46 and the coexistence of a systemic metabolic disorder, other associated conditions or dysmorphic features would lower the threshold for investigation as would a family history of consanguinity, stillbirths, multiple miscarriages, fertility problems, genital abnormalities, hernias, delayed puberty, genital surgery, unexplained deaths and the need for steroid replacement.…”
Section: Which Newborn Should Be Investigated?mentioning
confidence: 99%